The effect of management on land tenure in Hoedspruit, Limpopo Province - Shai, Given Felix (My University, 2017)
Recent changes in South Africa have exerted a lot of pressure on the government to redress the past injustices on the land redistribution among its citizens. The community of Hoedspruit is not excluded from the above challenges, hence the study on the effect of management of land tenure in Hoedspruit. The management of land tenure in Hoedspruit was fraught with challenges such as lack of clarity on policies, managerial skills, resources, institutional support, inadequate training programmes, lack of financial support, alternative strategy, monitoring and evaluation. This study also seeks to investigate the factors that hinder the effective management of land tenure. Data was obtained by means of questionnaires and semi-structured interviews. These were used to have a deeper understanding of the challenges that were encountered by the new land owners in the area of the study. The main findings of the study confirmed that there were challenges associated with the management of land tenure. Lack of financial support and relevant training were regarded as the main problems that hinder the management of land tenure in Hoedspruit. In conclusion, the study also suggested some strategies and recommendations that can enhance the effective management of land tenure in Hoedspruit.
Thesis (M. Dev.) -- University of Limpopo, 2017.
Keywords: Land redistribution; Land tenure; Land tenure -- South Africa -- Limpopo; Farm management -- South Africa -- Limpopo